(untitled) (Balneo and PRM Research Journal, 2024)
Abstract Amyotrophic lateral sclerosis (ALS) represents a progressive neurodegenerative disease that affects motor neurons in the brain and spinal cord leading to the impairment of voluntary muscle control and eventually death. It accounts for about 80%-90% of all motor neuron diseases, and is characterized by a marked variability in terms of clinical forms, genetics, survival rate and diagnostic particularities. A diagnosis of ALS or one of the variants comes with a great burden for the patient and patient’s family because of the high morbidity and mortality rate of this disorder. As a consequence, it is mandatory to optimize the accuracy of the diagnostic process of ALS spectrum for providing the best clinical management and quality of life for patients and avoiding diagnostic mistakes. Our review focuses on the general and particular aspects of ALS and its variants in an effort to improve the process of diagnosis, therapy and exclusion of mimics of this group of diseases and to provide the latest findings in this field. Keywords: amyotrophic lateral sclerosis, rehabilitation in ALS, flail leg, flail arm, progressive muscular atrophy.